2023
DOI: 10.1111/ibi.13201
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Little Penguin population sizes using automated acoustic monitoring and citizen science

Abstract: While automated recorders are becoming a favourable tool to monitor birds, methods to analyse the large amount of data generated and their reliability for estimating population size are still limited. In this study, I compared Little Penguins Eudyptula minor call detection between a trained researcher, amateur volunteers and an automated software, assessed which environmental factors affect call variability and detectability and determined the feasibility of automated recorders to estimate population sizes. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The island is uninhabited with a granite coastline and an open habitat dominated by indigenous grasses and patchy shrubs covering the lower areas. Long‐term monitoring has shown that most Little Penguin nests are located on the northern shore of the island (Colombelli‐Négrel 2015, 2020). During the October 2018 population census, 44 adult Little Penguins were recorded on the island (Colombelli‐Négrel 2019).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The island is uninhabited with a granite coastline and an open habitat dominated by indigenous grasses and patchy shrubs covering the lower areas. Long‐term monitoring has shown that most Little Penguin nests are located on the northern shore of the island (Colombelli‐Négrel 2015, 2020). During the October 2018 population census, 44 adult Little Penguins were recorded on the island (Colombelli‐Négrel 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Long‐term monitoring has shown that most Little Penguin nests are located on the northern shore of the island (Colombelli‐Négrel 2015, 2020). During the October 2018 population census, 44 adult Little Penguins were recorded on the island (Colombelli‐Négrel 2019). All other Little Penguin colonies previously located near Granite Island are now extinct (Colombelli‐Négrel & Kleindorfer 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations